Correlation of Oxford Classification Score with Early Response to Treatment in IgA Nephropathy: A Cross-Sectional Study - Mahnoor Ali; Syed Nayer Mahmud (Journal of the Dow University of Health Sciences)
Objective: To evaluate the correlation between the Oxford classification score and early response to treatment in Immunoglobulin A nephropathy (IgAN) in a single-center study in northern Pakistan. Methods: This cross-sectional study was conducted at the Department of Nephrology, Shifa International Hospital, Islamabad, from July 2024 to January 2025. Patients aged 18 to 65 years with biopsy-proven primary IgAN were included. Baseline demographic, clinical, and laboratory data, including serum creatinine, eGFR, and proteinuria, were recorded. Renal biopsies were assessed using Oxford classification, evaluating mesangial hypercellularity (M), endocapillary hypercellularity (E), segmental glomerulosclerosis (S), tubular atrophy/interstitial fibrosis (T) and crescents (C). Early treatment response was defined as a ≥50% reduction in proteinuria after three months. Results: Of total 30 patients, the median age was 30.5 (24.5 – 43.5) years. The Oxford classification revealed that 19 (63.3%) patients had M1 and S1 lesions, 16 (53.3%) had E0 lesions, and 12 (40.0%) exhibited T0 lesions. A significant reduction in proteinuria was observed after treatment (p-value < 0.001), with eGFR and serum albumin levels improving significantly (p-value 0.003 and p-value 0.023) respectively. T1-2 lesions demonstrated a strong negative correlation with eGFR (ρ = -0.760, p-value < 0.001), and E1 lesions were moderately correlated with proteinuria (ρ = 0.378, p-value 0.039). Treatment response was observed in 12 (40%) patients, but no significant associations were found with individual Oxford classification scores. Conclusion: A significant reduction in proteinuria and improvement in eGFR and albumin were observed post-treatment. Histopathological features correlated with renal outcomes, emphasizing their significance in predicting early treatment outcomes.